2010
DOI: 10.1248/jhs.56.275
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Change in Tissue Fatty Acid Composition When Dietary Soybean Oil Is Switched to Olive Oil

Abstract: This experiment characterizes the time-dependent changes of phospholipids of liver microsomes, plasma, and triglycerides of adipose tissue when olive oil is substituted for soybean oil in the American Institute of Nutrition 93 Growth (AIN 93G) diet. After 2 weeks of acclimation with 7% soybean oil diet, 108 male Sprague-Dawley rats were randomly assigned to be fed diets with either 7% or 15% soybean oil or olive oil. Fatty acids of adipose, blood plasma, and liver microsomes were analyzed every four days for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The lack of a statistically significant difference between high-fat diet and the control diet in biochemical and histopathological examination, suggest that oleic acid which has been in high fat diet content of soybean oil (13) and lard (14) would have protective effect (15). In another study, it was found that soybean oil decrease lipogenesis and liver fat density (16).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a statistically significant difference between high-fat diet and the control diet in biochemical and histopathological examination, suggest that oleic acid which has been in high fat diet content of soybean oil (13) and lard (14) would have protective effect (15). In another study, it was found that soybean oil decrease lipogenesis and liver fat density (16).…”
Section: Discussionmentioning
confidence: 99%
“…After being released from liver microsomal membrane, PUFA activate phospholipase A2 and favor oxidation of arachidonic acid by cytochrome P450 system [40]. In our previous study [12], olive oil promoted an increase in EPA and DHA in phospholipids. These long chain fatty acids are derived from α-linolenic acid through Δ6-desaturation and elongation steps.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid compositions of dietary oils are reflected into fatty acid compositions of membrane phospholipid, which are the strong biochemical indicators of dietary fatty acids [ 11 ]. Fatty acid compositions of three different tissues and, in particular, the MUFA and PUFA content are highly dependent on the fat composition of the diet by de novo synthesis or by elongation from fatty acids provided by the dietary fats [ 5 , 12 - 14 ]. Our results showed that a high level of linoleic acid in the diet induced an increase of linoleic acid with a concomitant decrease of oleic acid in liver phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower ARA phospholipid levels when comparing dietary n6-PUFArich diets with olive oil-rich diets have been observed in mice 25 and rats. 26 Hence, a combination of MUFA and n3-PUFA is a promising approach in order to diminish excessive n6-PUFA intake, to reach a more balanced n6/n3-PUFA ratio and thereby increasing n3-PUFA bioavailability.…”
Section: Introductionmentioning
confidence: 99%